Emotional demands as a risk factor for mental distress among nurses / Richieste emotive come fattore di rischio per il distress mentale tra gli infermieri - Balducci, Cristian; Avanzi, Lorenzo; Fraccaroli, Franco (La Medicina del Lavoro, 2014)
SUMMARY Background: Although it is widely acknowledged that in certain occupations emotional demands may be a critical phenomenon for workers’ health, this has been traditionally taken for granted and their role in the stress process has not often been directly assessed. Objectives: To examine the relationship between emotional demands and mental distress, adjusting for the potential effect of common psychosocial factors (workload, job control, social support, role stressors, and poor relationships) and personal psychological factors (i.e. having been diagnosed with anxiety or depressive disorder). Methods: A crosssectional study on a sample of nurses of the National Healthcare Service was carried out (N=256, 81.3% women). The psychosocial factors considered were assessed by means of widely known and validated scales. The examined health outcome (i.e. mental distress) was operationalized by means of the General Health Questionnaire (12item version). Covariates: gender, age, tenure and shiftwork. Analyses: a series of logistic regressions. Results: Exposure to emotional demands was a risk factor for mental distress. The resulting risk was not altered when adjusting for other psychosocial and personal factors. In the final model emotional demands, workload and role stressors, in addition to having been diagnosed with anxiety or depressive disorder, were significant risk factors for nurses’ mental distress. Conclusions: Emotional demands may substantially impact on nurses’ mental distress. These results give rise to concern in relation to workstress prevention in certain professions, given that emotional demands are not included in the most common psychosocial risk assessment tools currently available, which may then miss identifying an important precondition of work stress. RIASSUNTO «Richieste emotive come fattore di rischio per il distress mentale tra gli infermieri». Introduzione: Nonostante sia ampiamente riconosciuto che in certe occupazioni le richieste emotive sono un fenomeno critico per la salute dei lavoratori, ciò è stato spesso dato per scontato ed il loro ruolo nel processo dello stress da lavoro è stato raramente valutato in maniera diretta. Obiettivi: Esaminare la relazione tra richieste emotive e distress mentale, controllando per comuni fattori psicosociali (carico di lavoro, controllo, supporto sociale, stressors del ruolo e qualità delle relazioni interpersonali) e personali (aver ricevuto da un medico una diagnosi di disturbo d’ansia o depressione). Metodi: studio crosssectional su 256 infermiere (81,3% donne) del Servizio Sanitario Nazionale. I fattori psicosociali sono stati valutati attraverso scale validate e ampiamente conosciute. La variabile di esito è stata operativizzata con il General Health Questionnaire a 12 item. Covariate: genere, età, anzianità lavorativa e lavoro a turni. Le analisi sono consistite di una serie di regressioni logistiche. Risultati: L’esposizione a richieste emotive è risultata fattore di rischio per il distress mentale. Il rischio non veniva modificato aggiustando per gli altri fattori psicosociali e personali considerati. Nel modello finale le richieste emotive, il carico di lavoro e gli stressors del ruolo, oltre ad aver riportato una diagnosi di disturbo d’ansia o depressione, sono emersi come fattori di rischio per il distress mentale delle infermiere. Conclusioni: Le richieste emotive possono impattare sostanzialmente sul distress mentale delle infermiere. Questi risultati destano preoccupazione in relazione alla prevenzione dello stress in certe occupazioni, dato che le richieste emotive non sono considerate nella gran parte degli strumenti disponibili per valutare i rischi psicosociali, i quali quindi ignorano una determinante importante dello stress da lavoro.